Information Behaviour of Ghanaian Parents of Children with Autism Spectrum Disorder - Nimako, D.; Danquah, M.M.; Kankam, P.K. (Libres, 2025)
Background. In Ghana, parents of children with autism spectrum disorder (ASD) face significant information challenges, which greatly impact their ability to provide appropriate care and support for their children. Many parents struggle with limited access to reliable and culturally relevant information about ASD, including intervention strategies and available support services. These challenges prompted this study, as understanding the information needs of parents with ASD children is crucial in improving the access to credible information for enhancing the overall support system available to them. Objectives. This study aims to identify the information needs of parents of children with ASD in Ghana; examine the sources parents used to access ASD related information; assess information usage and satisfaction among parents; seek out the challenges in accessing ASD related information; and recommend strategies to improve information access for parents. Methods. The qualitative case study approach was employed, involving 41 parents of ASD children from two schools. Telephone and face-to-face interviews served as the data collection instrument. Data collected were analysed using the thematic approach. Results. Key findings are that the parents exhibiting diverse information needs sought for information in various forms and from different sources. They expressed dissatisfaction with the quality and quantity of information obtained and encountered numerous challenges in accessing supportive resources to help take care of their children with ASD. Contributions. This study recommends targeted strategies to enhance information behaviour among parents of children with ASD. Key recommendations include awareness of specific information needs, evaluating information sources, balancing information needs, navigating information overload and initiating government-led ASD information.
Research Article
Keywords: Ghanaian Parents; Children; Autism Spectrum Disorder